A digital twin of tropical dairy cattle reveals the impact of temperature stress on feeding behaviour - Kemp, Stephen J.; Salavatia, M.; Dhulipala, Ram; Paliwal, Ambica; Singh, Kanika; Shin, R.; Heo, T.; Kim, N.; Kipchirchir, Nelson; Gluecks, Ilona V.; Wambugu, Sospeter (International Livestock Research Institute, 2025)
Livestock are increasingly exposed to heat stress which impacts their welfare and productivity. This report describes the development of a digital twin representing the grazing behaviour, environment and heat stress of a group of crossbred dairy cattle in a Kenyan ranch. The digital representation revealed that feeding is significantly reduced during periods of high heat stress with some cattle being much more affected than others. Over a 40-day period, we observed some 500 minutes of grazing time lost due to heat stress by the most heat-susceptible cattle in comparison to the least affected animals. This approach offers a scalable phenotype proxy for animal adaptation to environmental stressors.